International Impacts on Social Policy Short Histories in Global Perspective - Nullmeier, Frank; González de Reufels, Delia; Obinger, Herbert (Global Dynamics of Social Policy, 2022)
This open access book consists of 39 short essays that exemplify how interactions between inter- and trans-national interdependencies and domestic factors have shaped the dynamics of social policy in various parts of the world at different points in time. Each chapter highlights a specific type of interdependence which has been identified to provide us with a nuanced understanding of specific social policy developments at discrete points in history. The volume is divided into four parts that are concerned with a particular type of cross-border interrelation. The four parts examine the impact on social policy of trade relations and economic crises, violence, international organisations and cross-border communication and migration. This book will be of interest to academics and postgraduate students in the field of social policy, global history and welfare state research from diverse disciplines: sociology, political science, history, law and economics.